Constructing Careers: The Value of Undergraduate Research in Developing Agriculture Industry-Ready Students - Nicole Volk; Cara Lawson; Laura Morgan Fischer; Joy N. Rumble (Journal of Applied Communications, 2025)
As career opportunities in the agricultural industry continue to increase, there is an ongoing need for trained graduates to meet workforce demands. Though technical knowledge is important, agribusiness organizations have emphasized the importance of higher-order behavioral skills, such as problem-solving, decision-making, organization, teamwork, and communication. Undergraduate research, broadly defined as scientific inquiry, creative activity, or scholarship which produces some original work from students, it also builds transferrable workforce skills. Using social constructivist and experiential learning theories, this qualitative case study explored the role of undergraduate student research in developing graduates who are prepared to meet the needs of industry and future careers through the perspectives of industry and university professionals. Participants thought that students with strong research skills would greatly benefit their future employers, regardless of that organization’s need for research. The following themes were identified in relation to the research questions: (1) Success in the workplace is more than technical knowledge; (2) Research skills are desirable workforce skills; and (3) Social science research can address agricultural issues alongside industry. Although participants’ experiences with research varied, they viewed undergraduate research as an opportunity for students to increase their workforce readiness by developing higher-order behavioral skills. Framing undergraduate research as an opportunity to intentionally network and build skills for their future careers may encourage more students to participate in research. However, faculty must be intentional when designing and delivering learning opportunities, taking time to understand students’ career goals, identifying topics of interest, and encouraging reflection.
Keywords: workforce development; undergraduate research; industry perspectives; social constructivism; experiential learning